Validasi Metode Penentuan Residu Pestisida Deltametrin pada Daun Teh - Surani, Surani; Asmoro, Cahyo Puji (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
The Instrument Chemistry Laboratory is a testing laboratory for lecturers, students, and the public who will apply for ISO 17025 accreditation. In accordance with ISO 17025 requirements, the tests carried out must use a validated analytical method. For this reason, this research aims to validate the analytical methods that will be used for measurements. In this study, a validation method was employed to determine deltamethrin pesticide residues in tea leaves (Camellia sinensis) using GC-FID. The validation parameters that were evaluated were precision, accuracy, linearity, LOD, and LOQ tests. The resulting value of the linearity test was r2 = 0.9988, precision test percent RSD = 3.08%, and accuracy test percent recovery = 98.84%. Based on the results of the data analysis, all the test parameters met the acceptance standard requirements. Therefore, the method validation carried out was valid. As for the tea leaf sample, the resulting concentration was 30.98 ppm with a %RSD value of 3.97%.